EFFECT OF TWO CHICKS WEIGHT ON SOME CHARACTERISTICS CARCASS OF COBB 700 BROILER AT AGE 42 DAYS 1- SOME CARCASS CHARACTERISTICS AND ITS LENGTHS - Zangana , Bushra S. (Diyala Agricultural Sciences Journal, 2013)
This study was carried out at the College of Agriculture – Baghdad University aiming the evaluation of two days old chicks weights 41.00 and 46.06g on carcass characteristics of broiler at age 42 day . The result obtained indicated the following :- It will be better in circumambient of breast , thigh ,body and breast fleshing , length of thigh bones and drumstic for chicks resultant from (H) comparison with (M) . There were consequential better in weight of cold carcasses and after frozen and thawing under temperature -18 c for carcass of birds resultant from (H) comparison with (M) . Predominant weights of the carcass main (breast , thigh , drumstic) and secondary cuts (neck , back , wing) after thawing for birds resultant from chicks (H) comparison with (M) with percent 8.41% and 6.96% respectively . It could be concluded that chicks (H) gives at 6 weeks carcass with pest characteristics like circumambient of breast , thigh also batter in body dimension and low of thawing loose comparison with chick (M)